Positive electrode material, secondary battery, and electronic device

By regulating the size and distribution of rod-shaped lithium phosphate grains of the olivine structure, its shortcomings in high-rate discharge and low-temperature performance are solved, and efficient discharge and low-temperature stability of the secondary battery are achieved.

CN119864414APending Publication Date: 2025-04-22NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510072134.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The olivine lithium phosphate cathode material has shortcomings in high-rate discharge and low-temperature performance, especially the problems of poor electron conductivity and slow ion diffusion rate, which affects the application of the material.

Method used

By regulating the length, diameter and aspect ratio of rod-shaped lithium phosphate grains of the olivine structure, it ensures that they are within a specific range, thereby improving the diffusion coefficient and path simplicity of the lithium ions, reducing lattice distortion and impurity ion blockage, and promoting the diffusion and charge transfer reaction of lithium ions.

Benefits of technology

The high-rate discharge performance and low-temperature performance of secondary batteries have been improved, the ionic and electronic conductivity of the material has been improved, and the insufficient performance of the material at high loads and low temperatures has been alleviated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864414A_ABST
    Figure CN119864414A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode material, a secondary battery and an electronic device. The positive electrode material is a rod-like crystal grain with an olivine structure; the average length of the positive electrode material is I nm, and I is more than or equal to 150 and less than or equal to 1000; the average cross section diameter of the positive electrode material is D nm, and D is more than or equal to 50 and less than or equal to 300; the length-diameter ratio of a single positive electrode material is P, based on the number of particles of the positive electrode material, the proportion of the number of particles with P not less than 1.5 and not more than 5 is A%, and A is not less than 50 and not more than 100. The positive electrode material provided by the invention is used for a secondary battery, can improve the diffusion coefficient of lithium ions, and has relatively good high-rate discharge performance and low-temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage technology, and in particular to a positive electrode material, a secondary battery and an electronic device. Background Art

[0002] The characteristics of the positive electrode material are one of the important factors that determine the discharge performance of secondary batteries. Olivine-type lithium phosphate has attracted widespread attention for its advantages such as high safety, low cost, stable charge and discharge platform, stable cycle performance and environmental friendliness. However, olivine structural materials have poor electronic conductivity and slow ion diffusion rate, which seriously hinders the application of materials. Therefore, it is urgent to provide secondary batteries with good rate performance and low-temperature discharge performance. Summary of the invention

[0003] The embodiments of the present application provide a positive electrode material, a secondary battery and an electronic device, which achieve excellent high-rate discharge performance while improving low-temperature performance.

[0004] In a first aspect, an embodiment of the present application provides a positive electrode material, which is a rod-shaped grain with an olivine structure; the average length of the positive electrode material is I nm, 150≤I≤1000; the average cross-sectional diameter of the positive electrode material is D nm, 50≤D≤300.

[0005] Based on the positive electrode material of the embodiment of the present application, the inventors found that when the positive electrode material is olivine-type rod-shaped lithium phosphate salt grains, and its average length and average cross-sectional diameter meet a specific range, its highly exposed (010) crystal plane can introduce a large number of lithium ion channels, thereby increasing the diffusion coefficient of lithium ions. At the same time, the path of the lithium ion diffusion direction is relatively short, which shortens the lithium ion diffusion path. The phenomenon that the one-dimensional lithium ion diffusion path of the olivine-type lithium phosphate salt is easily blocked by lattice distortion and impurity ions can be alleviated, and the charge transfer reaction of lithium ions in the electrolyte at the positive electrode / electrolyte interface can be promoted, thereby improving the high-rate discharge performance and low-temperature performance of the secondary battery.

[0006] In some embodiments, the aspect ratio of a single positive electrode material is P, and based on the number of positive electrode material particles, the number of particles with 1.5≤P≤5 accounts for A%, and 50≤A≤100. Meeting the above range can improve the high rate discharge performance and low temperature performance of the secondary battery.

[0007] In some embodiments, the positive electrode material satisfies at least one of the following conditions: (1) 500≤I≤1000; (2) 50≤D≤100; (3) 70≤A≤100. Based on the above embodiments, the present application can further improve the high rate discharge performance and low temperature performance of the secondary battery by adjusting the length, diameter and aspect ratio of the rod-shaped lithium phosphate salt particles to further meet the above ranges.

[0008] In some embodiments, based on the number of particles of the positive electrode material: the number of particles with 2≤P≤3 accounts for B%, 50≤B≤60; the number of particles with 3≤P≤5 accounts for C%, 20≤C≤50. Based on the above embodiments, the present application can improve the high rate discharge performance and low temperature performance of the secondary battery by controlling the distribution of lithium phosphate particles with a specific aspect ratio to meet the above range.

[0009] In some embodiments, the positive electrode material includes a lithium phosphate salt, and the chemical formula of the lithium phosphate salt is LiMPO4X; wherein the M element includes one or more of iron, manganese, cobalt or nickel, and the X element includes one or more of titanium, magnesium, vanadium, chromium, copper, zinc, yttrium, zirconium, niobium, molybdenum or tungsten. Based on the above embodiments, when the positive electrode material in this application adopts the above lithium phosphate salt and contains a specific metal element, the electronic structure of the material can be changed, and the doped metal atoms can form a solid solution with other elements, so that the impurity energy level is between the conduction band and the forbidden band to provide electronic conductivity; at the same time, doping can increase the lattice defects of the material, expand the diffusion channel of lithium ions, and reduce the resistance of lithium ion insertion / extraction, which is beneficial to improve the ionic and electronic conductivity of the material, thereby further improving the high-rate discharge performance and low-temperature performance of the secondary battery.

[0010] In some embodiments, the X element is selected from one or more of titanium, magnesium or vanadium; based on the mass of the positive electrode material, the mass proportion of the X element is x ppm, 1000≤x≤8000. Based on the above embodiments, the positive electrode material in the present application includes the above metal elements, and the mass proportion thereof is controlled to meet a specific range, which can further improve the diffusion coefficient of lithium ions, shorten the diffusion path of lithium ions, and promote the charge transfer reaction of lithium ions in the electrolyte at the positive electrode / electrolyte interface, thereby further improving the high rate discharge performance and low temperature performance of the secondary battery.

[0011] In some embodiments, the ratio of the average length I nm of the positive electrode material to the average cross-sectional diameter D nm of the positive electrode material is Q, 7≤(x / 100) 1 / 2 / 3+3Q≤18. Based on the above embodiments, the present application can further improve the high rate discharge performance of the secondary battery while improving the low temperature performance by adjusting the relationship between the mass ratio and the aspect ratio of the above metal elements and controlling the distribution coefficient of the metal elements in the positive electrode material grains.

[0012] In some embodiments, in the XRD spectrum of the positive electrode material, the peak intensity ratio of the (210) peak to the (101) peak is E, 0.38≤E≤0.40. Based on the above embodiments, in the XRD spectrum of the positive electrode material of the present application, when the peak intensity ratio of the two peaks meets the above range, the secondary battery has better high rate discharge performance and low temperature performance.

[0013] In some embodiments, the specific surface area of ​​the positive electrode material is F m 2 / g, 15≤F≤30. Based on the above embodiments, the present application can further improve the high rate discharge performance of the secondary battery while improving the low temperature performance by adjusting the specific surface area of ​​the positive electrode material to meet the above range.

[0014] In a second aspect, an embodiment of the present application provides a secondary battery, including a positive electrode plate, the positive electrode plate including a positive electrode collector and a positive electrode material layer located on at least one surface of the positive electrode collector, the positive electrode material layer including the above-mentioned positive electrode material.

[0015] In a third aspect, an embodiment of the present application provides an electronic device, which includes the secondary battery mentioned above. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0017] Figure 1 This is the XRD pattern of Examples 2-18 of the present application. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments and drawings. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0019] A first aspect of an embodiment of the present application provides a secondary battery, including a positive electrode, a negative electrode, an electrolyte and a separator.

[0020] positive electrode

[0021] <Cathode Materials>

[0022] One embodiment of the present application provides a lithium phosphate doped positive electrode material. The positive electrode material is a rod-shaped crystal with an olivine structure; the average length of the positive electrode material is I nm, 150≤I≤1000. Preferably, it is 500≤I≤1000. For example, the length of the positive electrode material may be 150, 264, 300, 441, 500, 602, 744, 800, 976, 1000 or a value within the range of any two of these values. The average cross-sectional diameter of the positive electrode material is Dnm, 50≤D≤300. Preferably, it is 50≤D≤100. For example, the cross-sectional diameter of the positive electrode material may be 50, 60, 100, 144, 197, 211, 256, 300 or a value within the range of any two of these values. The aspect ratio of a single positive electrode material is P, and based on the number of particles of the positive electrode material, the number of particles with 1.5≤P≤5 accounts for A%, and 50≤A≤100. Preferably, 70≤A≤100. For example, in the positive electrode material particles, the value of the percentage of particles with 1.5≤P≤5 can be 50, 56, 70, 79, 88, 90, 100 or a value in the range composed of any two of these values. When the positive electrode material is an olivine-type rod-shaped lithium phosphate salt particle, and its length, diameter and aspect ratio meet a specific range, the charge transfer reaction of lithium ions in the electrolyte at the positive electrode / electrolyte interface can be promoted, thereby improving the high rate discharge performance and low temperature performance of the secondary battery.

[0023] In some of the embodiments, based on the number of particles of the positive electrode material: the number of particles with 2≤P≤3 accounts for B%, 50≤B≤60. For example, the value of the percentage of the number of particles with 2≤P≤3 in the positive electrode material can be 50, 51, 54, 56, 57, 59, 60 or a value within the range composed of any two of these values. The number of particles with 3≤P≤5 accounts for C%, 20≤C≤50. For example, the value of the percentage of the number of particles with 3≤P≤5 in the positive electrode material can be 20, 26, 30, 33, 42, 48, 50 or a value within the range composed of any two of these values. The particle distribution of the lithium phosphate positive electrode material meets the above range, which can further improve the high rate discharge performance and low temperature performance of the secondary battery.

[0024] In some embodiments, the positive electrode material includes lithium phosphate salt, and the chemical formula of the lithium phosphate salt is LiMPO4X; wherein the M element includes one or more of iron, manganese, cobalt or nickel, and the X element includes one or more of titanium, magnesium, vanadium, chromium, copper, zinc, yttrium, zirconium, niobium, molybdenum or tungsten. When the above lithium phosphate positive electrode material is used and contains specific metal elements, the ionic and electronic conductivity of the material can be improved, thereby further improving the high-rate discharge performance of the secondary battery, while also improving the low-temperature performance.

[0025] In some embodiments, the X element is selected from one or more of titanium, magnesium or vanadium; based on the mass of the positive electrode material, the mass proportion of the X element is x ppm, 1000≤x≤8000. For example, the mass proportion of the X element in the mass of the positive electrode material can be 1000, 2248, 2882, 3928, 6270, 7624, 8000 or a value in the range of any two of these values. The lithium phosphate positive electrode material includes the above-mentioned metal elements, and the mass proportion thereof is controlled to meet a specific range, which can further improve the high rate discharge performance of the secondary battery while improving the low temperature performance.

[0026] In some embodiments, the ratio of the average length I nm of the positive electrode material to the average cross-sectional diameter Dnm of the positive electrode material is Q, 7≤(x / 100) 1 / 2 / 3+3Q≤18. In some embodiments, 8≤(x / 100) 1 / 2 / 3+3Q≤10. In some embodiments, 17≤(x / 100) 1 / 2 / 3+3Q≤18. In some embodiments, 12≤(x / 100) 1 / 2 / 3+3Q≤15. In some embodiments, 9≤(x / 100) 1 / 2 / 3+3Q≤13. In some embodiments, 11≤(x / 100) 1 / 2 / 3+3Q≤14. The distribution coefficient of the metal elements in the positive electrode material grains in the lithium phosphate positive electrode material satisfies the above range, which can further improve the high rate discharge performance of the secondary battery and improve the low temperature performance.

[0027] In some embodiments, the specific surface area of ​​the positive electrode material is F m 2 / g, 15≤F≤30. For example, the specific surface area of ​​the positive electrode material may be 15, 17, 18, 22, 23, 25, 30 or a value in the range formed by any two of these values. When the specific surface area of ​​the positive electrode material satisfies the above range, the high rate discharge performance of the secondary battery can be further improved while improving the low temperature performance.

[0028] <Method for preparing positive electrode material>

[0029] (1) lithium hydroxide monohydrate, ferrous sulfate heptahydrate, and ammonium dihydrogen phosphate are weighed in a molar ratio of nLi:nFe:nP, and the three substances are configured into an aqueous solution with a certain mass fraction, and the three solutions are slowly mixed while maintaining stirring conditions;

[0030] (2) adding a certain mass fraction of polyvinyl alcohol to synthesize lithium iron phosphate into a mixed solution as a dispersant, and adding an amount of glucose equal to the molar number of the synthesized lithium iron phosphate into the mixed solution as a grain growth controller;

[0031] (3) adjusting the pH of the reaction slurry and keeping the temperature for 5 h to 8 h to obtain lithium iron phosphate precursor A;

[0032] (4) filtering and washing the precursor A, mixing it with the carbon source, and spray drying it to obtain the lithium iron phosphate spray material B;

[0033] (5) The lithium iron phosphate spray material is calcined under a protective atmosphere to obtain a lithium iron phosphate positive electrode material.

[0034] <Positive electrode>

[0035] One embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector; the positive electrode material layer comprises the above-mentioned positive electrode material or the positive electrode material prepared by the above-mentioned method.

[0036] In some embodiments, the positive electrode material layer includes a positive electrode conductive material; the type of the positive electrode conductive material is not limited, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon materials such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.

[0037] In some embodiments, the positive electrode material layer includes a positive electrode binder; the type of the positive electrode binder is not particularly limited, and in the case of a coating method, any material that can be dissolved or dispersed in a liquid medium used in electrode manufacturing can be used. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, etc.; rubber polymers such as styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, etc.; thermoplastic elastomer polymers such as styrene-butadiene-styrene block copolymers or their hydrides, ethylene-propylene-diene terpolymers, styrene-ethylene-butadiene-ethylene copolymers, styrene-isoprene-styrene block copolymers or their hydrides; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, propylene-α-olefin copolymers; fluorine polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene-ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions, etc. The above positive electrode binders may be used alone or in any combination.

[0038] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, a mixed medium of alcohol and water or water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.

[0039] Thickeners are generally used to adjust the viscosity of the slurry. In the case of using an aqueous medium, the thickener and styrene-butadiene rubber emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.

[0040] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.

[0041] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode material layer, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings may include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.

[0042] negative electrode

[0043] The negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.

[0044] The negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), silicon, silicon-carbon composites, SiO w(0.5<w<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O 12 , Li-Al alloy or metallic lithium, etc. Optionally, the negative electrode active material may further include an amorphous carbon material, and the amorphous carbon may be soft carbon (low temperature calcined carbon), hard carbon, mesophase pitch carbide or calcined coke, etc.

[0045] The negative electrode material layer of the present application also includes a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the manufacture of the electrolyte or electrode. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.

[0046] The negative electrode material layer of the present application also includes a conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent can be at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene, and the above-mentioned carbon nanotubes can include but are not limited to at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes.

[0047] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode material layer is 30μm to 160μm. In the present application, the negative electrode mixture layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application has no special restrictions as long as the purpose of this application can be achieved.

[0048] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85g / cm 3 The present application has no particular limitation on the cold pressing pressure of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the cold pressing pressure of the negative electrode sheet can be 3 tons to 30 tons.

[0049] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the conductive layer, as long as the purpose of the present application can be achieved, for example, the thickness of the conductive layer is 1μm to 10μm.

[0050] Electrolyte

[0051] The electrolyte used in the secondary battery of the present application includes an electrolyte and a solvent for dissolving the electrolyte. The electrolyte may also include a lithium salt and a non-aqueous solvent. The present application does not particularly limit the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium trifluoromethanesulfonyl imide (LiTFSI), lithium bis (fluorosulfonyl) imide (LiFSI), lithium bis oxalate borate (LiBOB) or lithium difluoro oxalate borate (LiDFOB). Based on the mass of the electrolyte, the mass proportion of the lithium salt may be 8% to 15%, for example, the mass proportion of the lithium salt may be 8%, 9%, 10%, 11%, 12.5%, 13%, 15% or a range composed of any two of the values. The present application does not particularly limit the type of the above-mentioned non-aqueous solvent, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The carbonate compound may include but is not limited to at least one of a chain carbonate compound or a cyclic carbonate compound. The chain carbonate compound may include but is not limited to at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate or methyl ethyl carbonate. The cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate, propylene carbonate, butylene carbonate or ethylene ethylene carbonate. The carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone or caprolactone. The ether compound may include but is not limited to at least one of ethylene glycol dimethyl ether, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.

[0052] Diaphragm

[0053] In the present application, a diaphragm is usually provided between the positive electrode and the negative electrode, and the diaphragm is used to separate the positive electrode plate and the negative electrode plate to prevent internal short circuit of the secondary battery, allow electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process.

[0054] The present application has no particular restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of the separator may include at least one of woven membrane, non-woven membrane, microporous membrane, composite membrane, rolled membrane or spun membrane.

[0055] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0056] The pore size of the diaphragm in the present application is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In some embodiments, the thickness of the diaphragm is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the diaphragm is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the diaphragm is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the secondary battery can be ensured.

[0057] The present application further provides an electronic device, which includes a secondary battery of an embodiment of the present application. The electronic device includes but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0058] Example

[0059] Hereinafter, taking lithium-ion batteries as an example, examples and comparative examples are given to more specifically describe the implementation of the secondary battery of the present application. Those skilled in the art will understand that the preparation method described in the present application is only an example, and any other suitable preparation method is within the scope of the present application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0060] Example 1-1

[0061] (1) Preparation of positive electrode

[0062] <Preparation of positive electrode active material>

[0063] 1) lithium hydroxide monohydrate, ferrous sulfate heptahydrate, and ammonium dihydrogen phosphate were weighed at a molar ratio of nLi:nFe:nP=3:1:1, and the three substances were configured into aqueous solutions with mass fractions of 10%, 20%, and 30%, and the three solutions were slowly mixed while maintaining stirring conditions;

[0064] 2) adding polyvinyl alcohol with a mass fraction of 0.5% of the theoretical synthesized lithium iron phosphate as a dispersant to the mixed solution, and adding glucose in an amount equal to the molar number of the theoretical synthesized lithium iron phosphate as a grain growth controller;

[0065] 3) adjusting the pH of the reaction slurry to 9.0-9.5, and keeping the temperature at 150° C.-200° C. for 5 h-8 h to obtain lithium iron phosphate precursor A;

[0066] 4) Filtering and washing the precursor A, mixing it evenly with 10% by mass of a carbon source and 1000 ppm by mass of a magnesium dopant, and spray drying it to obtain a lithium iron phosphate spray material B;

[0067] 5) The lithium iron phosphate spray material is calcined under a protective atmosphere to obtain a lithium iron phosphate positive electrode material.

[0068] <Preparation of positive electrode sheet>

[0069] The lithium iron phosphate positive electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) prepared in the above steps are mixed in a mass ratio of 95:2:3, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, and dried to obtain a positive electrode sheet coated with a positive electrode mixture layer on one side. Repeat the above steps on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode mixture layer on both sides. By adjusting the cold pressing pressure, positive electrode sheets with different compaction densities and surface roughness can be obtained. After cold pressing, striping, and welding of the pole ears, a positive electrode sheet with a specification of 74mm×867mm is obtained.

[0070] (2) Preparation of electrolyte

[0071] In a dry argon atmosphere glove box, diethyl carbonate was used as a base solvent, lithium hexafluorophosphate (LiPF6) was dissolved in the base solvent, and vinylene carbonate was added as an additive to obtain an electrolyte. Among them, based on the mass of the electrolyte, the mass proportion of LiPF6 is 12.5%, and the mass proportion of vinylene carbonate is 2%.

[0072] (3) Preparation of negative electrode

[0073] Artificial graphite is used as the negative electrode active material. The negative electrode active material, styrene-butadiene rubber (SBR), polyacrylic acid (PAA), carbon nanotubes (CNT), and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 95.8:2.4:0.5:0.5:0.8, and then deionized water is added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 45wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried to obtain a negative electrode sheet coated with a negative electrode mixture layer on one side. Repeat the above steps on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode mixture layer on both sides. By adjusting the pressure of the cold pressing, negative electrode sheets with different compaction densities and surface roughness can be obtained. After cold pressing, stripping, and welding of the pole ears, a negative electrode sheet with a specification of 76.6mm×875mm is obtained.

[0074] (4) Preparation of diaphragm

[0075] A porous polyethylene film with a thickness of 15 μm was used as the separator.

[0076] (5) Preparation of lithium-ion batteries

[0077] The positive electrode sheet, negative electrode sheet and separator are stacked in order, the separator is placed between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in a packaging bag, dehydrated at 80°C, injected with electrolyte, and packaged. After the process of formation and hot pressing (formation at 80°C / 1~2.5Mpa, time 0.5h~2h), degassing, trimming, capacity testing and other processes, a lithium-ion battery is obtained.

[0078] <Test Method>

[0079] (1) Structural observation method

[0080] Take the lithium-ion battery prepared in the above steps, cut the positive electrode plate after ion polishing, and then use a scanning electron microscope to observe the crystal structure of the material layer on the surface of the plate and measure the particle length and cross-sectional diameter of the material. Measure 200 material particles, calculate their aspect ratios respectively, which is the P value; count the number of particles with different aspect ratios, which is the A value, B value, and C value; calculate the arithmetic mean of the length of the 200 material particles as the average length I nm, calculate the arithmetic mean of the cross-sectional diameter of the 200 material particles as the average cross-sectional diameter D nm, and calculate the arithmetic mean of the aspect ratio of the 200 material particles, which is the Q value.

[0081] Instrument model: ZEISS SEM, accelerating voltage: 0.1 kV~30 kV.

[0082] (2) Test method for the content of metal elements other than lithium

[0083] Take the lithium-ion battery prepared in the above steps, dissolve the positive electrode plate in a mixed solvent (for example, 0.4g of the positive electrode plate uses a mixed solvent of 5ml of aqua regia and 5ml of deionized water), fix the volume to 100mL, and then use an ICP analyzer to test the mass proportion of metal elements other than lithium in the solution.

[0084] (3) XRD image test method (diffraction peak intensity test method)

[0085] Take the lithium-ion battery prepared in the above steps, and perform X-ray diffraction analysis on the positive electrode to obtain an XRD pattern. Instrument model: Bruker D8 ADVANCE, target material: Cu Kα, scanning angle: 5° to 80°.

[0086] (4) 25℃ 4C rate discharge test

[0087] Take the lithium ion battery prepared in the above steps, charge it to 4.3V at a constant current of 0.2C rate at 25°C, then charge it at a constant voltage until the current is less than or equal to 0.05C, then let it stand for 30 minutes, and then discharge it to 2.5V at a constant current of 0.2C rate, and test to obtain the 0.2C rate discharge capacity of the lithium ion battery at 25°C; at 25°C, charge the lithium ion battery to 4.3V at a constant current of 0.2C rate, and then charge it at a constant voltage until the current is less than or equal to 0.05C; then let the battery stand for 60 minutes, and then discharge it to 2.5V at a constant current of 4C rate, and test to obtain the 4C rate discharge capacity of the lithium ion battery at 25°C.

[0088] 25℃4C rate discharge capacity retention rate (%)=25℃4C rate discharge capacity / 25℃0.2C rate discharge capacity×100%.

[0089] (5) Low temperature discharge performance test

[0090] Take the lithium-ion battery obtained in the above steps, place it in a high and low temperature box, adjust the temperature to 25°C, and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. The lithium-ion battery that has reached a constant temperature is discharged to 2.5V at a current constant current of 0.5C, then charged to 4.3V at a current constant current of 0.5C, and then charged to a current of 0.05C at the 4.3V voltage constant voltage. Also at a temperature of 25°C, discharge to 2.5V at a current constant current of 0.5C, and record the discharge capacity as the initial discharge capacity. At a temperature of 25°C, charge to 4.3V at a constant current of 0.5C, and then charge to a current of 0.05C at the 4.3V voltage constant voltage. Afterwards, place the lithium-ion battery at a temperature of 0°C and let it stand for 30 minutes so that the temperature of the lithium-ion battery is consistent with the external temperature. At 0°C, discharge to 2.5V at a current constant current of 0.5C, and record the discharge capacity as the low-temperature discharge capacity.

[0091] Low-temperature discharge capacity retention rate %=(low-temperature discharge capacity / initial discharge capacity)×100%.

[0092] The lithium-ion batteries of the following embodiments or comparative examples differ from those of embodiment 1-1 only in that materials with different average lengths, different average cross-sectional diameters, and different aspect ratios are screened according to Table 1 as positive electrode active materials of lithium-ion batteries. The performance test results of the lithium-ion batteries of the embodiments and comparative examples are shown in Table 1 below.

[0093] Table 1

[0094]

[0095] As can be seen from Table 1, the lithium-ion battery prepared in the embodiment of the present application, when the average length I nm of the positive electrode material satisfies 150≤I≤1000, the average cross-sectional diameter D nm of the positive electrode material satisfies 50≤D≤300, and the number of particles of 1.5≤P≤5 accounts for A% and satisfies 50≤A≤100, the high-rate discharge performance and low-temperature performance of the secondary battery can be improved. In particular, when the average length of the positive electrode material further satisfies 500≤I≤1000, the average cross-sectional diameter of the positive electrode material further satisfies 50≤D≤100, or the number of particles of 1.5≤P≤5 further satisfies 70≤A≤100, the high-rate discharge performance and low-temperature performance of the secondary battery can be further improved. In particular, when the number of particles of 2≤P≤3 in the positive electrode material satisfies 50≤B≤60 or the number of particles of 3≤P≤5 satisfies 20≤C≤50, the high-rate discharge performance and low-temperature performance of the secondary battery can be further improved.

[0096] The lithium-ion batteries of the following Examples 2-1 to 2-25 are different from those of Example 1-20 only in that the type of positive electrode material and the element content thereof are adjusted according to Table 2.

[0097] Table 2

[0098]

[0099] *In the above table, in Examples 2-5 to 2-7, the two X elements are mixed in a molar ratio of 1:1.

[0100] As can be seen from Table 2, the lithium-ion battery prepared in the embodiment of the present application can further improve the high-rate discharge performance and low-temperature performance of the secondary battery when the M element in the positive electrode material is adjusted to a specific type. When the X element in the positive electrode material is adjusted to a specific type, the high-rate discharge performance and low-temperature performance of the secondary battery can be further improved. When the mass ratio of the X element in the positive electrode material is adjusted to satisfy 1000≤x≤8000, the high-rate discharge performance and low-temperature performance of the secondary battery can be further improved. When the specific relationship between the mass ratio of the X element in the positive electrode material and the average length of the positive electrode material and the average cross-sectional diameter of the positive electrode material satisfies 7≤(x / 100) 1 / 2 / 3+3Q≤18, the high rate discharge performance and low temperature performance of the secondary battery can be further improved. When the peak intensity ratio of the characteristic peaks of the XRD spectrum of the positive electrode material satisfies 0.38≤E≤0.40, the high rate discharge performance and low temperature performance of the secondary battery can be further improved. When the specific surface area of ​​the positive electrode material satisfies 15≤F≤30, the high rate discharge performance and low temperature performance of the secondary battery can be further improved.

[0101] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A positive electrode material, characterized in that: The positive electrode material is a rod-shaped crystal grain with an olivine structure; the average length of the positive electrode material is I nm, 150≤I≤1000; the average cross-sectional diameter of the positive electrode material is D nm, 50≤D≤300.

2. The positive electrode material according to claim 1, characterized in that The aspect ratio of a single positive electrode material is P. Based on the number of particles of the positive electrode material, the number of particles with 1.5≤P≤5 accounts for A%, and 50≤A≤100.

3. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following conditions: (1)500≤I≤1000; (2)50≤D≤100; (3) The aspect ratio of a single positive electrode material is P. Based on the number of particles of the positive electrode material, the number of particles with 1.5≤P≤5 accounts for A%, and 70≤A≤100.

4. The positive electrode material according to claim 3, characterized in that Based on the number of particles of the cathode material: The number of particles with 2≤P≤3 accounts for B%, 50≤B≤60; The number of particles with 3≤P≤5 accounts for C%, and 20≤C≤50.

5. The positive electrode material according to any one of claims 1 to 4, characterized in that: The positive electrode material includes lithium phosphate salt, and the chemical formula of the lithium phosphate salt is LiMPO4X; The M element includes one or more of iron, manganese, cobalt or nickel, and the X element includes one or more of titanium, magnesium, vanadium, chromium, copper, zinc, yttrium, zirconium, niobium, molybdenum or tungsten.

6. The positive electrode material according to claim 5, characterized in that The X element is selected from one or more of titanium, magnesium or vanadium; Based on the mass of the positive electrode material, the mass proportion of the X element is x ppm, and the positive electrode material satisfies at least one of the following: (1)1000≤x≤8000; (2) The ratio of the average length I nm of the positive electrode material to the average cross-sectional diameter D nm of the positive electrode material is Q, 7≤(x / 100) 1 / 2 / 3+3Q≤18.

7. The positive electrode material according to any one of claims 1 to 4, characterized in that: In the XRD spectrum of the positive electrode material, the peak intensity ratio of the (210) peak to the (101) peak is E, 0.38≤E≤0.

40.

8. The positive electrode material according to any one of claims 1 to 4, characterized in that: The specific surface area of ​​the positive electrode material is Fm 2 / g, 15≤F≤30.

9. A secondary battery, characterized in that: A positive electrode sheet is included, wherein the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector; The positive electrode material layer comprises the positive electrode material according to any one of claims 1 to 8.

10. An electronic device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Cited By

  • Positive electrode material, secondary battery, and electronic device

    WO2026153200A1